Financial crisis, austerity, and electoral politics: European voter responses to the global economic collapse 2009-2013 - Magalhães, Pedro (2015)
Reprinted from “Special Issue: Financial Crisis, Austerity, and Electoral Politics,” 2014, Journal of Elections, Public Opinion and Parties, 24, 125-264